2022
DOI: 10.1136/bmjopen-2022-064142
|View full text |Cite
|
Sign up to set email alerts
|

Personalised Lung Cancer Screening (PLuS) study to assess the importance of coexisting chronic conditions to clinical practice and policy: protocol for a multicentre observational study

Abstract: IntroductionLung cancer is the leading cause of cancer death in the USA and worldwide, and lung cancer screening (LCS) with low-dose CT (LDCT) has the potential to improve lung cancer outcomes. A critical question is whether the ratio of potential benefits to harms found in prior LCS trials applies to an older and potentially sicker population. The Personalised Lung Cancer Screening (PLuS) study will help close this knowledge gap by leveraging real-world data to fully characterise LCS recipients. The principal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The Personalised Lung Cancer Screening study is an ongoing study using simulation models to estimate the effect of comorbidity, functional limitations, and impaired pulmonary function in LCS individuals. 37 …”
Section: Discussionmentioning
confidence: 99%
“…The Personalised Lung Cancer Screening study is an ongoing study using simulation models to estimate the effect of comorbidity, functional limitations, and impaired pulmonary function in LCS individuals. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Notably, a study from the National Cancer Database found that NSCLC patients residing in rural areas were at an increased risk of death versus those residing in urban settings [10]. Furthermore, racial and ethnic minority groups are disproportionately affected by comorbidities, and comorbidity burden can negatively affect NSCLC prognosis [11][12][13]. This analysis underscores the importance of considering multi-level clinical and sociodemographic factors that contribute to these inequities.…”
mentioning
confidence: 99%